A novel highly sensitive carbon-based HMPD/GC sensor electrode: copper ions analysis in flour and water samples - Durmus, Nagihan; Yilmaz, Ecir; Mulazimoglu, Aysen Demir; Mercimek, Bedrettin; Cukurovali, Alaaddin; Yilmaz, Ibrahim; Mulazimoglu, Ibrahim Ender (Desalination Publ, 2018)
In this research, (Z)-2-(2-(hydroxyimino)-2-(3-methyl-3-phenylcyclobutyl) ethyl)-3a,7a-dihy-dro-1H-isoindole-1,3(2H)-dione, HMPD molecule has been grafted to the glassy carbon (GC) electrode surface. The HMPD-modified GC electrode has been originally developed and it used for the quantitative determination of Cu(II) in flour and water samples. The modification steps have been performed using cyclic voltammetry (CV). CV, electrochemical impedance spectroscopy and scanning electron microscopy have been employed for the characterization processes. Cu(II) standard solutions changing from 1.0 x 10(-9) to 1.0 x 10(-3) M have been prepared and the corresponding peak currents have been measured. From the obtained data calibration equation has been calculated I-p = -1.555C(cu) + 15.86 which is having a 0.9974 correlation coefficient. 10.0 mL of flour and water samples have been mixed with 10.0 mL Britton-Robinson (BR) buffer solution (pH = 5.00) and HMPD/GC sensor electrode has been kept in these mixed solutions for 90 min. Differential pulse voltammetric (DPV) technique has been applied for the measurement of the peak currents. After the application of the developed sensor electrode for Cu(II) detection in flour and water samples, Cu(II) ion concentrations have been calculated from the obtained peak current values, 1.97 and 2.46 mu A. The Cu(II) ion concentrations have been calculated as 1.17 x 10(-9) and 2.41 x 10(-9) M, respectively.
5th International Conference on Sustainable Solid Waste Management (ATHENS) -- JUN 21-24, 2017 -- Athens, GREECE
Keywords: Chemical sensor electrode; Voltammetric techniques; HMPD/GC electrode; Surface modification; Surface characterization